Nalar Moderasi Beragama Muslim Merespon Covid-19 - Suprima Suprima; akmal rizki Gunawan; Rabiyyanur Lubis; Abdul Khoir; Acep Mulyadi; Siti Asiah (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2021)
This research is try to explain the reason for thinking moderation of Muslims, who are divided in two in response to Covid-19. On the one hand it is fatalistic and some are rationally liberal. The data obtained was analyzed qualitatively using religious moderation theory consisting of 4 aspects, namely; Fiqḥ Al-Maqāṣid (فقه المقاصد), Fiqḥ Al-Mālāt (فقه المالات), Fiqḥ Al-Muwāzanat (فقه الموازنة), and Fiqḥ Al-Awlawiyāt (فقه الأولويات). In this study the authors concluded as follows; First, in the context of Fiqh Al-Maqāṣid (فقه المقاصد) and Fiqḥ Al-Mālāt (فقه المالات), the reason for the moderation of a Muslim religion in the face of the Covid-19 pandemic cannot separate between ikhtiar ruhaniyah and scientific ikhtiar. That means it takes an integral understanding that is not partial. It is not enough to offer only religious methods, because human beings are physical beings. Nor is it enough just through medical because man is also a spiritual being. Second, in the context of Fiqḥ Al-Awlawiyāt (فقه الأولويات), should as a Muslim be required the ability to ground the reasoning of putting public logic above private logic, both in aspects of "ubudiyah" and "mu'amalah". Third, in the context of Fiqḥ Al-Muwāzanat (فقه الموازنة), should every Muslim put the reason hifẓ al-nafs (keeping the soul) among other maintenance.